Et rom hvor kroppen kan tre fram gjennom ulike uttrykk. Refleksjoner etter en pilotstudie om overvekt, kvinner og magedans - Trude Jægtvik; Kari Kvigne; Per Kristian Roghell (Nordisk Tidsskrift for Helseforskning, 2016)
A space where the body can emerge through various expressions. Reflections around a pilot study on overweight, women and belly dancing This article is based on the implementation of, and reflections on the experiences from a pilot study in belly dancing for obese women, as well as interviews with participants in connection with the course. The study had a qualitative approach. The movements in belly dance invite into a concentration towards the body along with others. This started processes on several levels. Acknowledgment of vulnerability seemed to be a strength, and an important basis for the women’s development. Academic communities internationally call for new approaches and methods in relation to obesity. It is natural to look at the body and movement in relation to health. If we however are going to create a space where the body can emerge through different expressions, is it then necessary to focus on health? Can the term health block a new insight? Maybe we also should concentrate more on attention to the body and its expressions?